Effects of insecticidal essential oil fumigations on physiological changes in cut Dendrobium sonia orchid flower - Pumnuan, Jarongsak; Khurnpoon, Lampan; Insung, Ammorn (My University, 2015)
This study investigated essential oil (EO) formulas with high insecticidal properties, but low physiological impacts on cut Dendrobium Sonia orchid flower. Fumigation toxicities of EOs from 18 medicinal plants at 2.0 and 3.0 μl/L air were examined against adults of thrips (Frankliniella schultzei) and larvae of mealybug (Pseudococcus jackbeardsleyi). The effective EO mixtures, optimal concentrations fumigation and air circulation periods were investigated. Then, field experiments were conducted, and changes in L*, a* and b* values, percentages of weight loss and anthocyanin contents of the EO-fumigated flower were observed and compared to the methyl bromide and control fumigations. The results showed that clove and cinnamon demonstrated high insecticidal properties against the insects (>85% mortality) and low physiological changes in the flower. In particular, fumigations with 2.0 μl/L air of a mixture between clove and cinnamon EOs (1:3) for 3 hr with 15- min air circulation demonstrated the highest thrips and mealybug mortalities (92.2 and 74.6%, respectively). The EO fumigation formula presented less impact on color change and anthocyanin content than methyl bromide fumigation which showed higher reduction of anthocyanin content (22.9 mg/100g FW) when compared to the control (13.6 mg/100g FW). The percentages of weight loss in the flower fumigated with EO, control and methyl bromide were about 10.4, 7.9 and 14.8%, respectively. In general, applications of EO at higher concentrations resulted in higher insect mortalities and more impacts on physiological changes which involved anthocyanin degradation and higher percentages of weight loss. Further studies might consider applications of clove and cinnamon EO formulas via other methods. In addition, revisions of the EO mixture can also be examined in order to obtain the most effective and environment friendly insect management approach.
Keywords: Fumigation; Insecticidal; Methyl bromide; Phytotoxicity